Vertical and spatial evaluation of the groundwater chemistry in the Central Nile Delta Quaternary aquifer to assess the effects of human activities and seawater intrusion - Salem, Zenhom E.; ElNahrawy, Abdelaziz; Attiah, Abdullah M.; Edokpayi, Joshua N. (Frontiers in Environmental Science, 2022)
Contaminants can be found in the groundwater through natural processes, such as seawater intrusion, or due to human activities that can adversely affect the quantity, quality, and distribution of the groundwater. In order to assess the influence of human activities and seawater intrusion on the groundwater chemistry in the Central Nile Delta region, groundwater was collected from 167 production wells, with depths of 15–120 m. In addition, eight soil-water samples were collected from depths of about 1 m. The groundwater samples were divided based on well depths into three zones: shallow zone (<40 m depth), intermediate zone (41–60 m depth), and deep zone (>60 m depth). The TDS, EC, pH, K+, Na+, Mg2+, Ca2+, Cl−, HCO3−, and SO42- were determined for all water samples. The groundwater samples with Cl of 100–200 mg/L and EC of 600–2,000 μs/cm represent mixing between freshwater and saltwater. The increase in TDS and concentrations of all major ions toward the northern parts reflected the impact of the seawater intrusion. The groundwater had an Na/Cl ratio of 0.46–2.75, indicating the influence of both seawater intrusion and anthropogenic activities on groundwater chemistry. In addition, the high Ca/Mg, Ca/SO4, and Ca/HCO3 ratios (>1) indicated that the groundwater was intruded by seawater. The obtained water types, the ionic ratios, and the saturation index results suggested that anthropogenic activities, water-rock interaction, infiltration, mineral weathering, and seawater intrusion are the main processes controlling the variation and evolution of groundwater chemistry.